A one pot one step combined radical and ring-opening route for the dual functionalization of starch in aqueous medium. (15th February 2021) - Meimoun, Julie; Wiatz, Vincent; Saint-Loup, René; Parcq, Julien; David, Adélina; Stoclet, Grégory; Gaucher, Valérie; Favrelle-Huret, Audrey; Bonnet, Fanny; Zinck, Philippe
Highlights: One pot one step dual functionalization of starch in aqueous medium was studied. Combination of free radical and ring-opening grafting chemistries was performed. Materials with elongation at break in the range 20–210 % were obtained. Abstract: Starch based materials are attractive bio-based alternative to fully synthetic polymers. Native starch has however limited thermoprocessability and properties and must be modified. In order to improve the properties of starch- graft -poly(butyl-acrylate- co -styrene) copolymers via a process as green as possible, we report herein a new method for the dual functionalization of the polysaccharide via a one pot one step reaction in aqueous medium combining free radical polymerizations and ring-opening chemistry. Poly(butyl acrylate) or poly(butyl acrylate- co -styrene) ( ca. 60 000 g/mol) and oligo(ε-caprolactone) were grafted on starch with a grafting percentage up to 75 %. The copolymers show two glass transition temperatures: one around 55−60 °C related to starch and a second attributed to the grafted vinyl polymers, from −46 °C to 20 °C depending on butyl acrylate/styrene ratio. The resulting dual functionalized materials exhibit excellent mechanical properties, with elongation at break in the range 20–210 %, while single functionalized starch shows less than 5 %.